SELECTING THE OPTIMUM PROJECT DELIVERY METHOD FOR GASOLINE SULFUR HYDROTREATING PROJECT AT RU-III PLAJU AND RU-VI BALONGAN REFINERIES OF PT KILANG PERTAMINA INTERNATIONAL (KPI) BY USING ANALYTIC HIERARCHY PROCESS (AHP) - Achmad Bastomi, Andry
PT Kilang Pertamina International (KPI), as a subsidiary of PT Pertamina (Persero), currently operates and fully administers the refinery business subholding, intends to build new Gasoline Sulfur Hydrotreater (GSH) unit to comply with the latest government regulation for Sulphur content of Gasoline shall be adjusted maximum 50 ppm by the end of 2027.